Rent sharing in China: Magnitude, heterogeneity and drivers - Wenjing Duan; Pedro S. Martins (Global Labor Organization (GLO), 2020)
Do firms in China share rents with their workers? We address this question by examining firm-level panel data covering virtually all manufacturing firms over the period 2000-2007, representing an average of 52 million workers per year. We find evidence of rent sharing (RS), with wage-profit elasticies of between 4% and 6%. These results are based on multiple instrumental variables, including firm-specific international trade shocks. We also present a number of complementary findings to understand better the nature of RS in the country: it involves an element of risk sharing, as wages also decrease when profits fall; RS is lower in regions with more latent competition from rural workers; higher minimum wages tend to reduce RS; and, while employer labour market power reduces wages, it increases RS. Overall, despite its importance, RS in China is smaller and more symmetric than in developed economies, which re ects the weaker bargaining power of its workers and the different nature of its labour market institutions.
Keywords: J31; J41; J50; 330; Wages; Bargaining; Monopsony